1999
DOI: 10.1364/josaa.16.002069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on the monochromatic aberrations of the human eye

Abstract: We measured the contrast sensitivity (CS) of a group of older subjects through natural pupils and compared the results with those from a group of younger subjects. We also measured each subject's monochromatic ocular wave-front aberrations using a crossed-cylinder aberroscope and calculated their modulation transfer functions (MTF's) and root-mean-squared (RMS) wave-front aberrations for fixed pupil diameters of 4 mm and 6 mm and for a natural pupil diameter. The CS at a natural pupil diameter and the MTF comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(85 citation statements)
references
References 33 publications
5
72
0
8
Order By: Relevance
“…5,6 Therefore, the total ocular aberration increases with age, leading to deterioration of optical quality in older subjects. [7][8][9][10] When the crystalline lens is replaced by an intraocular lens (IOL) in cataract surgery, further changes may occur. It has been shown that ocular higher-order aberration in pseudophakic eyes is comparable with that in phakic eyes of subjects of the same age.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Therefore, the total ocular aberration increases with age, leading to deterioration of optical quality in older subjects. [7][8][9][10] When the crystalline lens is replaced by an intraocular lens (IOL) in cataract surgery, further changes may occur. It has been shown that ocular higher-order aberration in pseudophakic eyes is comparable with that in phakic eyes of subjects of the same age.…”
Section: Introductionmentioning
confidence: 99%
“…As the eye ages, aberrations and scattering are increased (Ijspeert et al, 1990;Siik et al, 1992;Whitaker et al, 1993;van den Berg, 1995;Hennelly et al, 1998;Guirao et al, 1999;Calver et al, 1999;Kuroda et al, 2002;Fujikado et al, 2004), thus resulting in LSF broadening. In this study, since primarily the central region of the double-pass LSF was examined, aberrations and diffraction likely had a dominant role in determining the LSF shape.…”
Section: Discussionmentioning
confidence: 99%
“…Es ist bekannt, dass die Aberrationen des menschlichen Auges mit zunehmendem Alter signifikant ansteigen und sich dadurch die Abbildungsqualität des Auges verschlechtert (Calver et al 1999, McLellan et al 2001, Marcos 2002, Amano et al 2004. Diese altersabhängige Zunahme der Aberrationen ist vor allem bei größeren Pupillendurchmessern gut zu beobachten (Oshika et al 1999 (Klyce et al 2004).…”
Section: Alter Der Probandenunclassified
“…Die Einteilung der Pupillendurchmesser von 4 und 6 mm wird häufig verwendet (Calver et al 1999, Ninomiya et al 2002, Amano et al 2004, Artal et al 2004, Montés-Micó et al 2004a). Die Pupillendurchmesser von 2, 4 und 6 mm wurden beispielsweise auch von …”
Section: Pupillendurchmesserunclassified